2013
DOI: 10.1200/jco.2012.47.4189
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase II Trial of Onartuzumab in Combination With Erlotinib in Patients With Advanced Non–Small-Cell Lung Cancer

Abstract: Onartuzumab plus erlotinib was associated with improved PFS and OS in the MET-positive population. These results combined with the worse outcomes observed in MET-negative patients treated with onartuzumab highlight the importance of diagnostic testing in drug development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
395
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 449 publications
(408 citation statements)
references
References 18 publications
11
395
1
1
Order By: Relevance
“…This statement was evidence based and supported by 7 studies, 107e113 comprising 1 MA, 107 1 phase II randomized controlled trial, 109 1 PCS, 110 and 4 RCSs. 108,111e113 All included studies were assessed for quality and none were found to have methodologic flaws that would raise concerns about the studies' finding (SDC Table 18).…”
Section: Lindeman Et Al 140mentioning
confidence: 89%
See 1 more Smart Citation
“…This statement was evidence based and supported by 7 studies, 107e113 comprising 1 MA, 107 1 phase II randomized controlled trial, 109 1 PCS, 110 and 4 RCSs. 108,111e113 All included studies were assessed for quality and none were found to have methodologic flaws that would raise concerns about the studies' finding (SDC Table 18).…”
Section: Lindeman Et Al 140mentioning
confidence: 89%
“…107 A frequently used commercially available antibody, particularly in clinical trials, is the CONFIRM anti-total MET (SP44) rabbit monoclonal primary antibody (Ventana Medical Systems, Tucson, Arizona) directed against a membranous and cytoplasmic epitope of MET. 109 At the time of publication, it remains unclear whether total MET or phosphoMET protein overexpression represents a reliable indicator of MET activation. Both MET IHC and FISH are not predictive of efficacy of onartuzumab combined with erlotinib in advanced NSCLC patients.…”
Section: Lung Cancer Molecular Testing Guideline Updatementioning
confidence: 99%
“…Recently, the need for biomarkers when targeting the HGF/cMET pathway has become apparent, with the finding that patients with NSCLC with low Met expression do worse when receiving onartuzumab (a monoclonal antibody targeting Met) + erlotinib than erlotinib + placebo [95]. It was proposed by Spigel and colleagues that abstract 4005).…”
Section: A Requirement For Biomarkersmentioning
confidence: 99%
“…Clinical development of onartuzumab was pursued in NSCLC before gastric cancer. A randomized phase II trial with relapsed NSCLC patients revealed that onartuzumab together with the EGFR TKI erlotinib conferred a better PFS and OS compared with erlotinib alone in MET-positive cases, which were defined prospectively as those in which more than 50 % of tumor cells were positive for MET expression by immunohistochemistry [58]. In contrast, a detrimental effect of the combination therapy compared with erlotinib alone was observed in MET-negative patients.…”
Section: Targeting Of the Hgf-met Axis By Monoclonal Antibodiesmentioning
confidence: 99%